SONOGRAPHIC REFERENCE LUMINAL DIAMETER OF THE ABDOMINAL AORTA AMONG SUBJECTS IN NIGERIA - S. OKPALEKE, MICHAEL; C. IKAMAISE, VALENTINE; K. AGWU, KENNETH; C. UGWU, ANTHONY; P. OGOLODOM, MICHAEL (Innovare Journal of Medical Sciences, 2021)
Objective: The objective of the study was to develop a reference luminal diameter (LD) of the abdominal aorta (AA) in Abuja, Nigeria. Methods: The LD of the AA of 422 male and female healthy subjects was measured sonographically using standard protocol. The relationship between age, body mass index (BMI), gender, and the LD of the AA was determined in the subjects. Statistical analysis was performed by the Student’s t-test and Pearson’s correlation coefficient at p < 0.05 level of significance. Results: The values of the LD of the AA in the healthy subjects were 15.16 ± 0.55 mm in males and 15.15 ± 0.55 mm in females. The 5th and 95th percentile normal reference limits of the AA were 14.20–16.10 mm, respectively. There were no significant differences in the LD measurements in male and female subjects. Age correlated strongly positively with LD (ɼ=0.90) of the AA in both genders. BMI showed weak positive correlation with LD (ɼ=0.136) of the AA in female healthy subjects only. Conclusion: The reference LD of the AA in the study population was 15.16 ± 0.55 mm in males and 15.15 ± 0.55 mm in females. The LD of the AA increased proportionately with age.